2013
DOI: 10.1016/j.jbiosc.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Development of genetic transformation and heterologous expression system in carboxydotrophic thermophilic acetogen Moorella thermoacetica

Abstract: To develop a microbial production platform based on hydrogen and carbon dioxide, a genetic transformation system for the thermophilic acetogen Moorella thermoacetica ATCC39073 was developed. The uracil auxotrophic strain dpyrF was constructed by disrupting pyrF for orotate monophosphate decarboxylase. The transformation plasmids were methylated by restriction methylases of M. thermoacetica to avoid the decomposition of introduced plasmids by restriction-modification system. Reintroduction of native pyrF into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 27 publications
0
78
0
Order By: Relevance
“…In the ΔpduL1::ldh mutant, the acetate yield was almost the same as that of the wild-type strain. The lactate yield, which was only 0.036 mol/mol, was comparable to that of the mutant M. thermoacetica C31, in which only T-ldh was introduced into the ΔpyrF parental mutant strain (14). In the ΔpduL2::ldh mutant, the lactate yield increased significantly to 0.73 mol/mol, and the acetate yield decreased to 0.77 mol/mol.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…In the ΔpduL1::ldh mutant, the acetate yield was almost the same as that of the wild-type strain. The lactate yield, which was only 0.036 mol/mol, was comparable to that of the mutant M. thermoacetica C31, in which only T-ldh was introduced into the ΔpyrF parental mutant strain (14). In the ΔpduL2::ldh mutant, the lactate yield increased significantly to 0.73 mol/mol, and the acetate yield decreased to 0.77 mol/mol.…”
Section: Resultsmentioning
confidence: 77%
“…In previous studies, we constructed a mutant that produced lactate from fructose by introducing an exogenous lactate dehydrogenase gene into M. thermoacetica. However, the lactate yield was significantly lower than the acetate yield (14). This result demonstrated that the acetate-producing pathway of M. thermoacetica should be disrupted for the efficient production of target metabolites.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…However, there has been remarkable progress in the development of genetic systems for numerous industrially important anaerobes, especially clostridia, in recent years. Protocols for gene deletion via double crossover homologous recombination were recently developed for the syngas fermenting C. ljungdahlii [39 ] and M. thermoacetica [40][41][42]. Uracil-auxotrophic mutants of M. thermoacetica [41 ] and C. thermocellum [43] were constructed allowing for both positive-and counter-selection of desired recombinants.…”
Section: Advances In Genetic Manipulation Toolsmentioning
confidence: 99%
“…Protocols for gene deletion via double crossover homologous recombination were recently developed for the syngas fermenting C. ljungdahlii [39 ] and M. thermoacetica [40][41][42]. Uracil-auxotrophic mutants of M. thermoacetica [41 ] and C. thermocellum [43] were constructed allowing for both positive-and counter-selection of desired recombinants. Moreover, methods employing bacterial group II intron for gene deletion [44,45,46 ] and a Bacillus subtilis resolvase [47-49] were developed as universal genetic tools for Clostridium species.…”
Section: Advances In Genetic Manipulation Toolsmentioning
confidence: 99%